ANALYSIS ON THE DIFFERENCES IN EFL LEARNERS’ DEMOTIVATING FACTORS AFTER COVID 19 PANDEMIC - Reza Anggriyashati Adara; Onin Najmudin (Ta'dib, 2020)
Abstract: The change in the learning environment as what happen ed in the aftermath of COVID 19 pandemic can lead to learners’ demotivation. The present study aims to analyze how COVID 19 pandemic can affect the differences in demotivation factors of a group of EFL learners. Therefore, a set of questionnaires were   distributed before and during COVID19 pandemic. In addition, semi-structured interviews were conducted to gain deeper insights on the matter. The results suggest significant differences in demotivational factors that affect the respondents before and after COVID19 pandemic. Before the pandemic, inadequate school facilities were the most demotivating factor. After the pandemic, test scores become the most demotivating factor among the respondents. However, teachers’' related factors and learning materials still relatively affect the respondents after the pandemic. Besides, online learning was found to be one of the demotivational factors among the respondents as they feel deprived from real life inter-action and burdened with lack of stable internet connection and suitable gadgets for online learning. The results suggest that changing the learning environment can affect learners’ demotivation and motivation. Thus, it seems imperative for the teachers to be able to adapt their approach and materials to suit changing conditions especially during the pandemicAbstrak: Perubahan lingkungan belajar yang terjadi pasca pandemi COVID 19 dapat menyebabkan penurunan motivasi peserta didik. Penelitian ini bertujuan untuk menganalisis bagaimana pandemi COVID 19 dapat mempengaruhi perbedaan faktor demotivasi pada kelompok peserta didik EFL. Oleh karena itu, serangkaian kuesioner dibagikan sebelum dan selama pandemi COVID19. Selain itu, wawancara semi-terstruktur dilakukan untuk mendapatkan pemahaman yang lebih dalam tentang masalah tersebut. Hasil penelitian menunjukkan perbedaan signifikan pada faktor demotivasi yang mempengaruhi responden sebelum dan sesudah pandemi COVID19. Sebelum pandemi, fasilitas sekolah yang tidak memadai merupakan faktor yang paling menurunkan motivasi. Setelah pandemi, skor tes menjadi faktor yang paling mendemotivasi responden. Namun, faktor guru dan materi pembelajaran masih relatif mempengaruhi responden setelah pandemi. Selain itu, pembelajaran online ditemukan sebagai salah satu faktor demotivasi di kalangan responden karena mereka merasa kehilangan interaksi di kehidupan nyata dan dibebani dengan kurangnya koneksi internet yang stabil dan gadget yang sesuai untuk pembelajaran online. Hasil penelitian menunjukkan bahwa mengubah lingkungan belajar dapat mempengaruhi motivasi dan motivasi peserta didik. Oleh karena itu, sangat penting bagi para guru untuk dapat menyesuaikan pendekatan dan materi mereka agar sesuai dengan kondisi yang berubah terutama selama pandemi